Relationship of Lennox–Gastaut syndrome with perinatal event: A cross-sectional study - Kumar, Achal (J Pediatr Neurosci, 2015)
INTRODUCTION: About one-half of children with Lennox–Gastaut syndrome (LGS) have history of birth hypoxia or other perinatal event but the knowledge about clinical, radiological profile and severity of epilepsy in these children as compared to those without a perinatal event is not known. MATERIALS AND METHODS: Thirty-one children with LGS were enrolled in this study and divided into two groups: One group with the perinatal event and other group without evidence of the perinatal event. We hypothesized that LGS with the perinatal event will have an early age of onset of LGS, more motor deficits and abnormal brain magnetic resonance imaging (MRI) and more severe epilepsy. RESULTS: There were 17 children in the perinatal event group and 14 in the other group. The mean age of onset of illness was significantly earlier in the perinatal event group (P < 0.05). More children in the perinatal event group had delayed milestones (P < 0.05), had higher seizure frequency (P < 0.05) however; there was no significant difference in number of anti-epileptic drugs consumed, motor deficits or MRI abnormalities. CONCLUSION: LGS children with the perinatal event have more severe epilepsy with early onset of disease and delayed milestones. History of perinatal insult in these children may help in predicting prognosis in LGS.